Microwave Assisted Synthesis and Sintering of Ba0.5Sr0.5Co0.8Fe0.2O3-δ Perovskite - Nuernberg,Rafael Bianchini (2015)
Ba0.5Sr0.5Co0.8Fe0.2O3-δ (BSCF) perovskite-type oxide is currently one of the most promising materials for applications in solid-oxide fuel cells (SOFCs), protonic ceramic fuel cells (PCFCs), oxygen separation membranes, and catalytic membranes for methane conversion. BSCF powder synthesis has received considerable attention and new synthesis methods have been proposed to obtain nanoscale powders with high chemical homogeneity. In this study, BSCF perovskite powder has been successfully prepared by microwave assisted combustion in aqueous solution. The synthesized powder was characterized by DSC, BET, XRD, and SEM. BSCF powder presented phase homogeneity, high specific surface area (9.93 g/m2) and nanometric crystallite size (23nm). The microwave sintering has been conducted in different conditions of dwell time and temperature. The influence of the temperature and the dwell time on microstructure was evaluated by optical microscopy. The results showed that microwave sintering could achieve the same densification compared to conventional sintering with only 10% of processing time. This shorter processing time has resulted in a reduction of grain size of up to 46.5%, compared to conventional sintering.